Subtemporal Transtentorial Approach in Mesencephalic and Perimesencephalic Lesions in Children—A Series of 20 Patients. Issue 4 (4th September 2019) - Spennato, Pietro; Chiaramonte, Carmela; Russo, Carmela; Onorini, Nicola; Mirone, Giuseppe; Mazio, Federica; Di Martino, Giuliana; Parlato, Raffaele Stefano; Cinalli, Giuseppe
Abstract: BACKGROUND: Midbrain and surrounding areas are among the most difficult regions to surgically approach in neurosurgery. The subtemporal approach is a well-known neurosurgical approach that is rarely described in children. OBJECTIVE: To assess the feasibility, advantages, and disadvantages of subtemporal approach in children. METHODS: A total of 20 pediatric patients with intra-axial tumors involving the lateral midbrain or superior cerebellar peduncle or with extra-axial tumors in the middle incisural space/Meckel cave underwent subtemporal transtentorial approaches with the aim to remove (16 cases) or biopsy (4 cases) their lesions. These cases were retrospectively reviewed and the surgical approach described. RESULTS: Total resection was achieved in 11 patients. In the 4 patients who underwent biopsies, a diagnosis was obtained. A total of 5 patients presented non-neoplastic lesions (dermoid tumors or cavernomas). A total of 9 patients harbored low-grade tumors and 6 high-grade tumors. Patients with low-grade tumors and non-neoplastic lesions are all alive with no evidence of disease or stable residue. Four patients affected by high grade tumors died. No patient suffered permanent neurological deficits related to the surgical approach. Three patients presented temporary neurological deficits following the procedure: one case of strabismus, one case of aphasia and hemiparesis, secondary to delayed, transient thrombosis of the Labbé vein, and 1 case of trigeminal neuralgia. CONCLUSION: The subtemporal approach represents a feasible approach for mesencephalic and perimesencephalic lesions in children. It provides an ample and direct access, with excellent outcomes and acceptable postoperative morbidity.